Peran Humas PLTA Poso Dalam Menjaga Citra Baik Perusahaan di Tengah Masa Konflik Dengan Petani Padi Di Desa Toinasa - Setiawan, I Gusti Ngurah Putu (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2024)
This study aims to determine the role of the Poso Hydroelectric Power Plant Public Relations in maintaining the company's image. The method used in this study is descriptive qualitative, data collection techniques used are observation and interviews. The informants in this study numbered four people, who were selected by purposive sampling. The data analysis techniques in this study were data reduction, data display, and conclusion drawing. Based on the results of the data analysis conducted, the results of the study showed that in the role of the Poso Hydroelectric Power Plant Public Relations in dealing with the conflict with rice farmers in Toinasa village in an effort to maintain the company's good image. As an expert advisor, namely by advising on the replacement of farmers' land from previously rice fields to ponds or freshwater pools, a communication facilitator, namely conveying complaints about the first rice profit change to money in the second profit change, a problem-solving process facilitator, namely the Poso Hydroelectric Power Plant public relations, granting permission and accompanying the community around Lake Poso to carry out Megilu activities in the company area, and finally, the Poso Hydroelectric Power Plant public relations communication technician conveyed positive things done by the company through social media, namely Facebook and YouTube.